Nitrogen, phosphorus and potassium formula fertilization model of Lonicera japonica Thunb in hilly and gully Loess Plateau of China - Xiaofeng Jiang; Jianguo Guo; Shangzhong Li; Yuan Chen; Zhaohui Shi; Ping Xu; Bo Dong; Jiali Chen; Qing Fang; Yusheng Zhai (PLoS ONE, 2025)
Formula fertilization has been shown to effectively increase both yield and economic profit in medicinal plants. Lonicera japonica Thunb (L. japonica) is a significant medicinal plant; however, no studies have yet investigated the impact of formula fertilization on its performance. Therefore, the objective of this study is to establish models for enhancing the yield of L. japonica through formula fertilization using various ratios of nitrogen (N), phosphorus (P), and potassium (K) in the primary production areas of the hilly and gully Loess Plateau in China. A ‘3414’ formula fertilization trial was conducted, examining different doses and ratios of N, P, and K applied to L. japonica.Fertilizer was applied to a small pit, 30 cm deep, surrounding the root of each tree. The spacing between plants and rows was maintained at 1.0 m x 1.0 m. A fertilizer model was developed by calculating and comparing the yield and economic profit of the plants. The results indicated that the application of nitrogen (N), phosphorus (P), and potassium (K) in the soil significantly improved yield. Phosphorus (P) was identified as the primary limiting factor affecting yield. The output-to-investment ratio of the N2P2K3 fertilizer was significantly reduced. The fertilizer effect function can be expressed as: Y = 296.66 - 0.81X1 + 11.53X2 + 4.05X3 - 0.051X1² - 0.60X2² - 0.28X3² + 0.13X1×X2 + 0.20X1×X3 - 0.029X2×X3. The recommended doses of nitrogen (N), phosphorus (P), and potassium (K) fertilizers are 18.25–26.75 g, 6.27–8.73 g, and 10.04–13.96 g per plant, respectively.The application of formula fertilizer in this study resulted in a notable increase in yield and economic benefit, with improvements of 38.18% and an additional 0.3729 USD per plant, respectively. These findings significantly contribute to the production of L. japonica, enhancing both yield and profitability in specific geographical conditions suited for cultivating economic plants.